Quasi-Colonial Bodies: An Analysis of the Reproductive Lives of Poor Black and Racially Subjugated Women - Bridges, Khiara M. (Columbia Journal of Gender and Law, 2009)
This Article analyzes the relationship between the struggle for the recognition of Black women’s reproductive rights in the United States and the fight for racial justice. Specifically, it argues that the problematization of poor Black women’s fertility–evidenced by the depiction of single Black motherhood as a national crisis,1 the condemnation of poor Black women who rely on public assistance, and the portrayal of their children as an embryonic “criminal class”-ought to be understood as a form of contempt for Black women’s reproductive rights. Differently stated, the lack of acknowledgment in legal, political, and popular discourse that motherhood is a legitimate choice for poor Black women demonstrates that their right to reproduce is disparaged. Further, this censure of poor Black women’s fertility ought to be understood not only as a failure of the reproductive rights movement, but also as a matter of racial injustice. That is, the struggle of poor Black women to have their reproductive choices respected is a struggle for racial equality. Conceptualizing Black women’s reproductive rights struggles as a racial injustice may seem counterintuitive. This is in part due to the widespread exclusion of gender-related issues from social movements for racial equality. Many Black feminists have noted that the paradigmatic subject of racial justice movements has been the Black man, while the paradigmatic subject of gender justice movements has been the White woman. As political scientist Shatema Threadcraft recently commented, “that our understanding of contemporary race problems is dominated by issues of criminal justice and public education, and that our understanding of gender politics assumes that the biggest struggles that women have faced are around access to legitimate public roles, reveals troubling gender and racial bias, respectively.”